Investigating seasonal methane emissions in Northern California using airborne measurements and inverse modeling. Issue 22 (18th November 2016) - Johnson, Matthew S.; Xi, Xin; Jeong, Seongeun; Yates, Emma L.; Iraci, Laura T.; Tanaka, Tomoaki; Loewenstein, Max; Tadić, Jovan M.; Fischer, Marc L.
Abstract: Seasonal methane (CH4 ) emissions in Northern California are evaluated during this study by using airborne measurement data and inverse model simulations. This research applies Alpha Jet Atmospheric eXperiment (AJAX) measurements obtained during January–February 2013, July 2014, and October–November 2014 over the San Francisco Bay Area (SFBA) and northern San Joaquin Valley (SJV) in order to constrain seasonal CH4 emissions in Northern California. The California Greenhouse Gas Emissions Measurement (CALGEM) a priori emission inventory was applied in conjunction with the Weather Research and Forecasting and Stochastic Time‐Inverted Lagrangian Transport model and inverse modeling techniques to optimize CH4 emissions. Comparing model‐predicted CH4 mixing ratios with airborne measurements, we find substantial underestimates suggesting that CH4 emissions were likely larger than the year 2008 a priori CALGEM emission inventory in Northern California. Using AJAX measurements to optimize a priori emissions resulted in CH4 flux estimates from the SFBA/SJV of 1.77 ± 0.41, 0.83 ± 0.31, and 1.06 ± 0.39 Tg yr −1 when using winter, summer, and fall flight data, respectively. Averaging seasonal a posteriori emission estimates (weighted by posterior uncertainties) results in SFBA/SJV annual CH4 emissions of 1.28 ± 0.38 Tg yr −1 . A posteriori uncertainties are reduced more effectively in the SFBA/SJV region compared to state‐wide values indicating that the airborne measurements are most sensitive to emissions in this region. A posteriori estimates during this study suggest that dairy livestock was the source with the largest increase relative to the a priori CALGEM emission inventory during all seasons. Key Points: Airborne measurements are used to constrain source apportioned methane (CH4 ) emissions in Northern California Seasonal measurements resulted in SFBA/SJV CH4 emission estimates ranging from 0.83 ± 0.31 to 1.77 ± 0.41 Tg yr −1 Emission estimates suggest that existing bottom‐up CH4 emission inventories may underestimate fluxes in California